Multidimensional relative poverty of rural women: Measurement, dynamics, and influencing factors in China - Peng, Yan (Frontiers in Psychology, 2022)
Background China has eliminated absolute poverty; however, relative poverty still exists. Specifically, the characteristic group of rural women is affected by traditional gender concepts and behavioral norms, and rural women are often relatively deprived of economics, rights, abilities, and information. Objective Therefore, studying their relative poverty is crucial for realizing the overall development of China and the shared prosperity of farmers. Methods This study utilizes the multidimensional poverty theory to construct an analytical framework for the multidimensional relative poverty of rural households using the Alkire-Foster multidimensional measurement method and the tracking survey data of the “China Family Tracking Survey” from 2010 to 2016. From the “individual perspective,” the six dimensions of economy, health, humanities, spiritual life, social relations, and rights are used to measure and compare the relative poverty of women and men in rural households in China. Results The results showed that the relative poverty of women in rural households is extensive and broader, especially in the economic, humanities, and rights dimensions, and is much higher than that of men. Education level, physical health, ideology, and family status are the primary factors affecting the multidimensional relative poverty of women. Conclusion This study finds that the relative poverty of rural women exists within the family and it is multi-dimensional. This finding provides a reference for promoting well-rounded human development and achieving common prosperity for everyone.